ANALISIS KEMAS ULANG INFORMASI FORMAT TEKS KE AUDIOVISUAL (STUDI KASUS VIDEO RESENSI DI KANAL YOUTUBE PERPUSTAKAAN UNIVERSITAS SANATA DHARMA YOGYAKARTA) - Rika Widiana; Labibah Zain (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The purpose of this study was to know the process of producing book reviews in audiovisual format at the Sanata Dharma University Library in Yogyakarta. This type of research is classified as qualitative descriptive. Collecting data using observation, interview, and documentation techniques. The data analysis technique used in this study was the data analysis model of Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. Test the credibility of the research data using triangulation and member checks. The results of this study indicate that, in general, it can be concluded that first, in the process of production of visual audio reviews some of the planning strategies done, the development of the library movie maker team, the individual movie maker, was prepared through several written and spoken tests, and good budgeting of the meeting records as referencing the production process, he set of books to be reviewed, the concept stage, the concept and the location for the shoot. The production of the stage (1) preproduction; a) preparation, b) counter-culture concept, a location, c) budgeting, and d) planning the feedback. (2) production process; and post-production.